2008
DOI: 10.1111/j.1741-1130.2008.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Disability in the Context of a South African Population

Abstract: Childhood disabilities, including intellectual disabilities (ID), are thought to occur in 5–17% of children in developing countries around the world. In order to identify and describe the childhood disabilities occurring in a rural South African population, as well as the context in which they occur, a study was carried out in the Bushbuckridge district in the poor northeast part of the country. Altogether, 6,692 children were screened in their homes in eight villages using the Ten Questions questionnaire. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 9 publications
(15 reference statements)
3
32
0
Order By: Relevance
“…Service providers as well as primary caregivers reported on the special needs of children with disabilities and stated that these were often described in terms of lack of access to assistive devices such as wheelchairs, hearing aids, communication aids, specialized seating and standing frames (Hartley et al, 2005;Saetermoe, Gómez, Bámaca, & Gallardo, 2004) which can potentially impact negatively on children's physiological needs in terms of restricted mobility and limitations of self-care (Hartley et al, 2005). Poverty affected the families' possibilities of accessing rehabilitation and health care for their children with disabilities as transport to health care sites was often seen as too expensive; this was also described from both the primary caregiver's perspective as well as the service provider's perspective (Hartley et al, 2005;Kromberg et al, 2008;Saloojee, Phohole, Saloojee, & Ijsselmuiden, 2007;Yousafzai et al, 2003). The need of improved oral hygiene was described in one article (Shoaib et al, 2006) where the primary care givers revealed that children with intellectual impairment had significantly poorer oral hygiene when compared to typically developing children.…”
Section: Insert Table 3 About Herementioning
confidence: 99%
See 1 more Smart Citation
“…Service providers as well as primary caregivers reported on the special needs of children with disabilities and stated that these were often described in terms of lack of access to assistive devices such as wheelchairs, hearing aids, communication aids, specialized seating and standing frames (Hartley et al, 2005;Saetermoe, Gómez, Bámaca, & Gallardo, 2004) which can potentially impact negatively on children's physiological needs in terms of restricted mobility and limitations of self-care (Hartley et al, 2005). Poverty affected the families' possibilities of accessing rehabilitation and health care for their children with disabilities as transport to health care sites was often seen as too expensive; this was also described from both the primary caregiver's perspective as well as the service provider's perspective (Hartley et al, 2005;Kromberg et al, 2008;Saloojee, Phohole, Saloojee, & Ijsselmuiden, 2007;Yousafzai et al, 2003). The need of improved oral hygiene was described in one article (Shoaib et al, 2006) where the primary care givers revealed that children with intellectual impairment had significantly poorer oral hygiene when compared to typically developing children.…”
Section: Insert Table 3 About Herementioning
confidence: 99%
“…Misinformation about disability was highlighted in one study taken from the primary care giver's perspective, where mothers in the sample held the belief that their child's disability was temporary and looked for ways to "cure" the disability and make the child "normal" . Proper diagnoses and subsequent medical treatment at an early age was emphasized in several articles from both the primary caregivers and the service provider's perspectives (Hartley et al, 2005;Kromberg et al, 2008;Penny, Zulianello, Dreise, & Steenbeek, 2007). In some cases, as reported from both the service providers' and primary caregivers' perspective, receiving a correct diagnosis took a significant amount of time, which exacerbated the condition (Saetermoe et al, 2004).…”
Section: Insert Table 3 About Herementioning
confidence: 99%
“…These have typically been reported among parents in non-western countries, or among immigrants from nonwestern countries (e.g., Brolan et al, 2014;Mirza et al, 2009;Scior, Addai-Davis, Kenyon, & Sheridan, 2014). Although there are some reported claims by traditional healers about their ability to cure such disorders, Kromberg et al (2008) argue that the evidence is mostly anecdotal. Although there are some reported claims by traditional healers about their ability to cure such disorders, Kromberg et al (2008) argue that the evidence is mostly anecdotal.…”
Section: Introductionmentioning
confidence: 99%
“…[1] However, a study in a rural South African (SA) population reported the prevalence to be 3.6%. [2] The most common cause of ID in SA is fetal alcohol syndrome, which occurs at the highest rate in the world and at epidemic proportions in some communities in the Western Cape Province. [3] Fragile X syndrome (FXS) is the most common inherited cause of ID in all populations.…”
mentioning
confidence: 99%